Influence of concentration of vanadium in zinc oxide on structural and optical properties with lower concentration - Wang Li-Wei (2009)
ZnO films doped with different vanadium concentrations are deposited onto glass substrates by dc reactive magnetron sputtering using a zinc target doped with vanadium. The vanadium concentrations are examined by energy dispersive spectroscopy (EDS) and the charge state of vanadium in ZnO thin films is characterized by x-ray photoelectron spectroscopy. The results of x-ray diffraction (XRD) show that all the films have a wurtzite structure and grow mainly in the c-axis orientation. The grain size and residual stress in the deposited films are estimated by fitting the XRD results. The optical properties of the films are studied by measuring the transmittance. The optical constants (refractive index and extinction coefficient) and the film thickness are obtained by fitting the transmittance. All the results are discussed in relation with the doping of the vanadium.